Política regulatória e participação: um estudo sobre as audiências públicas na ANA e na ANEEL - Franco, Maria Salles Coelho de Mello (2016)
The present study intends to evaluate citizen participation in the decision making process of some Brazilian institutions assigned for regulating certain economic sectors in the country. Some regulatory agencies activities are analysed, highlighting the issues concerning independence and control of these organs. We focus on some international bodies guidelines regarding regulation via regulatory agencies, as well as some national bodies studies on the subject. In addition, the relevant legislation and the debates elaborated by the academia are demonstrated. Specifically, the study aims to evaluate public hearings empirically in the regulatory decision-making process of two federal regulatory agencies - the National Water Agency (ANA) and the National Electric Energy Agency (ANEEL). It seeks to identify (i) Who are the participants in the public hearings held by the agencies; (Ii) At what point in the regulatory decision-making process are the mechanisms for public deliberation inserted, and (iii) what is the justification for it - Who, When and Why? The results of the empirical analysis collected call attention to the necessary care to be employed in the practice of public hearings. It is evident that the malfunctioning of these instruments may affect the fulfilment of the purpose for which they were instituted. It is reiterated that the way in which social participation is practiced through public hearings in regulatory agencies is decisive for considerations about the legitimacy of regulatory decision making in these bodies.